2x*3x=10*(10x+10)

Simple and best practice solution for 2x*3x=10*(10x+10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x*3x=10*(10x+10) equation:


Simplifying
2x * 3x = 10(10x + 10)

Reorder the terms for easier multiplication:
2 * 3x * x = 10(10x + 10)

Multiply 2 * 3
6x * x = 10(10x + 10)

Multiply x * x
6x2 = 10(10x + 10)

Reorder the terms:
6x2 = 10(10 + 10x)
6x2 = (10 * 10 + 10x * 10)
6x2 = (100 + 100x)

Solving
6x2 = 100 + 100x

Solving for variable 'x'.

Reorder the terms:
-100 + -100x + 6x2 = 100 + 100x + -100 + -100x

Reorder the terms:
-100 + -100x + 6x2 = 100 + -100 + 100x + -100x

Combine like terms: 100 + -100 = 0
-100 + -100x + 6x2 = 0 + 100x + -100x
-100 + -100x + 6x2 = 100x + -100x

Combine like terms: 100x + -100x = 0
-100 + -100x + 6x2 = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(-50 + -50x + 3x2) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-50 + -50x + 3x2)' equal to zero and attempt to solve: Simplifying -50 + -50x + 3x2 = 0 Solving -50 + -50x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. -16.66666667 + -16.66666667x + x2 = 0 Move the constant term to the right: Add '16.66666667' to each side of the equation. -16.66666667 + -16.66666667x + 16.66666667 + x2 = 0 + 16.66666667 Reorder the terms: -16.66666667 + 16.66666667 + -16.66666667x + x2 = 0 + 16.66666667 Combine like terms: -16.66666667 + 16.66666667 = 0.00000000 0.00000000 + -16.66666667x + x2 = 0 + 16.66666667 -16.66666667x + x2 = 0 + 16.66666667 Combine like terms: 0 + 16.66666667 = 16.66666667 -16.66666667x + x2 = 16.66666667 The x term is -16.66666667x. Take half its coefficient (-8.333333335). Square it (69.44444447) and add it to both sides. Add '69.44444447' to each side of the equation. -16.66666667x + 69.44444447 + x2 = 16.66666667 + 69.44444447 Reorder the terms: 69.44444447 + -16.66666667x + x2 = 16.66666667 + 69.44444447 Combine like terms: 16.66666667 + 69.44444447 = 86.11111114 69.44444447 + -16.66666667x + x2 = 86.11111114 Factor a perfect square on the left side: (x + -8.333333335)(x + -8.333333335) = 86.11111114 Calculate the square root of the right side: 9.279607273 Break this problem into two subproblems by setting (x + -8.333333335) equal to 9.279607273 and -9.279607273.

Subproblem 1

x + -8.333333335 = 9.279607273 Simplifying x + -8.333333335 = 9.279607273 Reorder the terms: -8.333333335 + x = 9.279607273 Solving -8.333333335 + x = 9.279607273 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8.333333335' to each side of the equation. -8.333333335 + 8.333333335 + x = 9.279607273 + 8.333333335 Combine like terms: -8.333333335 + 8.333333335 = 0.000000000 0.000000000 + x = 9.279607273 + 8.333333335 x = 9.279607273 + 8.333333335 Combine like terms: 9.279607273 + 8.333333335 = 17.612940608 x = 17.612940608 Simplifying x = 17.612940608

Subproblem 2

x + -8.333333335 = -9.279607273 Simplifying x + -8.333333335 = -9.279607273 Reorder the terms: -8.333333335 + x = -9.279607273 Solving -8.333333335 + x = -9.279607273 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8.333333335' to each side of the equation. -8.333333335 + 8.333333335 + x = -9.279607273 + 8.333333335 Combine like terms: -8.333333335 + 8.333333335 = 0.000000000 0.000000000 + x = -9.279607273 + 8.333333335 x = -9.279607273 + 8.333333335 Combine like terms: -9.279607273 + 8.333333335 = -0.946273938 x = -0.946273938 Simplifying x = -0.946273938

Solution

The solution to the problem is based on the solutions from the subproblems. x = {17.612940608, -0.946273938}

Solution

x = {17.612940608, -0.946273938}

See similar equations:

| 1/3x-15/120x= | | 0=2x^2+11x+21 | | -7(7x-3)+1=-49x+22 | | 22x-45=93 | | 0.75(2x-5)=0.50(x+2) | | 2x-4=3(x+6) | | X(x+3x)=8(8+(x+2)) | | 64-x=73-2x | | log[4]2*x=0 | | a(7x+3)=b-21x | | y-4=30 | | 7*49=x*8x | | (x^2-1)+2(x^2-1)-15=0 | | 55=-0.8x+72 | | 0=x^2-12x+40 | | 2w^2-3w=5 | | 20x+3700=25x+3500 | | 10*19=x*5x | | 2y+3x-30x+2y= | | 10*19=5x*5 | | X^2-2=264 | | 6.1x-3+x-1.1= | | 4n+8=6 | | z^2+100=-20z | | x^2+8x-76=0 | | m=-3/4;(11,-3) | | -90z-0.8=-100z+1.6 | | (x-10)+(3X-6)=0 | | 30x^2+37x-8=-18 | | 2x*3x=110 | | X/5-8-10 | | 3x-0.05=36.05 |

Equations solver categories